Respuesta :
3x - 2x + 4 = 5x - 4x - 8
First, let's focus on the left side of the problem (3x - 2x + 4). Let's subtract 3x - 2x which will get us 1, and since a variable by itself is considered 1, we can just put the variable.
[tex]1 + 4 = 5x - 4x - 8[/tex]
Second, now let's focus on the right side of the problem (5x - 4x - 8). Subtract 5x - 4x to once again get 1. Replace it with the variable and leave the rest.
[tex]x = 4 = x - 8[/tex]
Third, we can now cancel out x on each side. This will leave us with 4 = -8, which is false, meaning that there is no solution to this problem.
[tex]\fbox {D) No Solution} [/tex]
First, let's focus on the left side of the problem (3x - 2x + 4). Let's subtract 3x - 2x which will get us 1, and since a variable by itself is considered 1, we can just put the variable.
[tex]1 + 4 = 5x - 4x - 8[/tex]
Second, now let's focus on the right side of the problem (5x - 4x - 8). Subtract 5x - 4x to once again get 1. Replace it with the variable and leave the rest.
[tex]x = 4 = x - 8[/tex]
Third, we can now cancel out x on each side. This will leave us with 4 = -8, which is false, meaning that there is no solution to this problem.
[tex]\fbox {D) No Solution} [/tex]